The Role of Environmental, Social, and Governance Disclosure in Moderating the Influence of Green Intellectual Capital on Company Value - Rivaldy, Mohamad Dhandy; Jayanti, Dwi (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the role of Environmental, Social, and Governance (ESG) disclosure in moderating the effect of Green Intellectual Capital (GIC) on company value. One of the ongoing problems faced by the mining sector is that while the mining industry plays a strategic role in the Indonesian economy, its operations have a significant environmental impact, such as pollution and environmental damage, which reduces the value of the company. This study uses a population of mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. A total of 19 samples were used. Data analysis techniques used Moderated Regression Analysis, using IIBM SPSS Statistics V.27. The results indicate that Green Relational Capital (GRC) has a significant positive impact on Firm Value. However, Green Human Capital (GHC) and Green Structural Capital (GSC) do not significantly influence Firm Value. Additionally, ESG disclosure strengthens the relationship between GRC and Firm Value but does not strengthen the relationship between GHC and GSC.